An Analysis of Chronotype and Cognitive Function in Pre-Clinical Medical Students at Universitas Airlangga - Hana Evangelin Prayogo; Wardah Rahmatul Islamiyah; Irfiansyah Irwadi; Sita Setyowatie (AKSONA, 2026)
Highlight: The intermediate chronotype was most common among 2020-2021 medical students at Universitas Airlangga, followed by the morning type and the evening type No significant differences in TMT A, TMT B, or PVT scores were observed among the morning, intermediate, and evening chronotypes. Chronotype showed no significant relationship with cognitive outcomes, likely because medical students adapt to rigorous demands requiring sustained focus throughout the day.   ABSTRACT Introduction: Chronotype refers to an individual’s predisposition to engage in activities at specific times of the day. Numerous studies have explored the relationship between chronotype and cognitive function, yet the findings vary across different populations. Objective: This study aimed to identify chronotypes among medical students at Universitas Airlangga and to assess differences in cognitive function and attentional performance between these chronotypes. Methods: We selected participants using a stratified random sampling technique, focusing on cognitive function, attention, and chronotype. Those who met the inclusion criteria provided informed consent and completed the Morningness-Eveningness Questionnaire to determine their chronotype. A total of 65 participants completed the questionnaire and then underwent Trail Making Tests (TMT) A and B at times tailored to their chronotypes: 08:00-10:00 for morning types, 16:00-18:00 for evening types, and 12:00-13:00 for intermediate types. The Psychomotor Vigilance Test (PVT) was uniformly administered between 08:00-10:00. Data were collected and analyzed using Kruskal-Wallis and one-way ANOVA. Results: Of the 65 participants, 18 were identified as morning types, 42 as intermediate types, and 5 as evening types. No significant differences were observed in TMT A or B performance (p > 0.05). Similarly, the PVT results, which assessed lapses, false starts, and average reaction time, showed no significant differences among the three chronotypes (p > 0.05). Conclusion: The intermediate chronotype was the most prevalent among medical students at Universitas Airlangga, followed by morning and evening types. No significant differences were observes in TMT and PVT outcomes across the chronotypes.